If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(9y + -2) + -1(7y + 5) = 0 Reorder the terms: 6(-2 + 9y) + -1(7y + 5) = 0 (-2 * 6 + 9y * 6) + -1(7y + 5) = 0 (-12 + 54y) + -1(7y + 5) = 0 Reorder the terms: -12 + 54y + -1(5 + 7y) = 0 -12 + 54y + (5 * -1 + 7y * -1) = 0 -12 + 54y + (-5 + -7y) = 0 Reorder the terms: -12 + -5 + 54y + -7y = 0 Combine like terms: -12 + -5 = -17 -17 + 54y + -7y = 0 Combine like terms: 54y + -7y = 47y -17 + 47y = 0 Solving -17 + 47y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + 47y = 0 + 17 Combine like terms: -17 + 17 = 0 0 + 47y = 0 + 17 47y = 0 + 17 Combine like terms: 0 + 17 = 17 47y = 17 Divide each side by '47'. y = 0.3617021277 Simplifying y = 0.3617021277
| x^2+1+2x-5x=0 | | x^2+1+2+5=0 | | 12x+5=y | | 3(2d-5)=-27 | | 3ab-15a-7b+35= | | 6(5+x)=30 | | 5(2l+3)=75 | | 12x+5x+5x=y | | 8x-(3x+14)=31 | | 30+24=54 | | 4(x+5)+33=6x-2(x-9) | | -3(x+4)=-5(x-2)-4 | | 0.19y+3=y-0.6 | | (2y-2)-y=4 | | y=-2x^2+4x-5 | | 5x+2(3-4x)= | | 3150.048=6.28r^2+626.116r | | 18(x+1+7z)= | | 8(7s-2)=3(s+5) | | 3x+1=-3x+2 | | 9z^2+24z+16=0 | | y=16t^2-56t+33 | | 3+5e=7 | | 150(m)=2800 | | y=3x-5z | | xy+8x+5y+40= | | 3x+-5y=21 | | 5n-7=-2 | | 3r+1=4r | | -4c+-8=24 | | 4.5(m)=35 | | 12+6g=36 |